MODEL SIR (SUSCEPTIBLE, INFECTED, REMOVED) PENYEBARAN COVID-19 DI PROVINSI PAPUA BARAT: MODEL SIR (SUSCEPTIBLE, INFECTED, REMOVED) PENYEBARAN COVID-19 DI PROVINSI PAPUA BARAT - Triono Wahyu Diamtoro; Tri Widjajanti Widjajanti; Dariani Matualage (FMIPA Universitas Papua, 2021)
Coronavirus Disease 2019 (COVID-19) is an infectious disease that has been declared a global pandemic by the World Health Organization (WHO). Indonesia is one of the countries affected by this disease and has spread to all provinces including West Papua Province. The purpose of writing this article is to determine a model for the spread of COVID-19 in West Papua, to analyze the point of equilibrium and stability and to determine the basic reproduction number R_0 model. The model used is the SIR epidemiological model and to analyze the equilibrium point and data collection, the author used the Mapple 13 application. The result of this study are a mathematical model based on the assumptions of the spread of COVID-19 in West Papua namely:dS/dt=-βSI/N.dI/dt=βSI/N-αI.dR/dt=αI.The equilibrium obtained based on the equilibrium analysis is the non-endemic equilibrium point, namely E=(S_0,I_0,R_0 )=(N,0,0)which is categorized as stabil neutral. The basic reproduction number (R_0 ) obtained based on the SIR COVID-19 model in West Papua isR_0=β/αwith R_0=1,2. Because the value of R_0>1 means that the spread of COVID-19 in West Papua will increase to become an epidemic. Keywords: SIR, COVID-19, Equilibrium Point, Basic Reproduction Number.